Термодинамическая оценка возможности протекания реакций силикатообразования в системах Аl₂O₃∙2SiO₂∙2H₂O – CaCO₃ – MgCO₃ и Аl₂O₃∙2SiO₂∙2H₂O – CaCO₃ – MgCO₃ – С - Винниченко, Варвара Ивановна; Виценко, Наталья Юрьевна; Рязанов, Александр Николаевич (НТУ "ХПИ", 2016)
Представлены результаты термодинамических исследований возможности образования при тепловой обработке первичных клинкерных минералов, способных взаимодействовать с водой в процессе набирания прочности доломитового цемента. В качестве основных компонентов сырьевой смеси приняты отходы доломита и отходы обогащения углей. Выполнены сравнительные исследования термодинамической возможности протекания реакций с появлением двухкальциевого силиката при наличии в исходных компонентах органической составляющей и без нее. Теоретически установлено, что наличие в смеси углерода способствует термодинамической вероятности снижения температуры начала протекания реакции образования двухкальциевого силиката.

Dolomite cements currently saline soluble which makes them uncompetitive due to higher prices salt. Although fired of dolomite clinker requires significantly less expenditure of thermal energy to the process. The results of thermodynamic analysis capabilities formation during heat treatment of the primary clinker minerals capable of reacting with the water during the strength development of cement dolomite. The main components of the raw mixture made of dolomite wastes and waste coal enrichment. Made comparative studies of reactions thermodynamic possibility with the advent of dicalcium silicate in the presence of a source component and organic components without it. It was found that the most likely to have a reaction to the result of the course which also formed of dicalcium silicate, tricalcium aluminate and calcium monoaluminate. This fact indicates that in a mixture of dolomite and waste coal tailings during firing clinker minerals can be formed that can gain their strength when mixing with water. It is found that the appearance of the organic component in the composition of the raw mix helps reduce the onset temperature of the chemical reaction. On the basis of theoretical research suggests that waste dolomite and waste coal enrichment can be considered as a promising component for binders dolomite.
Thermodynamic assessment of the possibility of occurrence of silicate formation reactions in systems Аl₂O₃∙2SiO₂∙2H₂O – CaCO₃ – MgCO₃ and Аl₂O₃∙2SiO₂∙2H₂O – CaCO₃ – MgCO₃ – С
Keywords: отход доломита; отходы обогащения углей; обжиг; энергия Гиббса; реакции; двухкальциевый силикат; углерод; снижение температуры; термодинамическая вероятность; waste dolomite; coal tailings; roasting; Gibbs energy; dicalcium silicate; carbon; drop in temperature; thermodynamic probability